Influential Factors of Investors’ Perceptions on Investment Decisions in Mutual Funds - Thapa, Bhim Kumar; Paudel, Ramesh Rasik; Khanal, Mohan; Chaulagain, Rajesh Kumar (International Journal of Social Sciences and Management, 2025)
Purpose- The objective of this study is to identify the factors that influence investors' perceptions and investment decisions by examining investment objectives (IO), Investment Returns (IR), investment structure (IS), and Investment Horizon (IH) on Investment Decisions (ID) for mutual fund investments in Nepal. This study seeks to provide valuable insights for fund managers, investors, and policymakers in the Nepalese mutual fund market. Design/Methodology/Approach- Data from 386 Nepalese mutual fund investors was collected quantitatively using a structured questionnaire. Analytical statistical approaches were utilized in structural equation modeling using AMOS. Path and mediation studies explored investment goals, returns, structure, horizon, and choices. Validity and reliability tests like Cronbach's Alpha protected constructs. The model fit was evaluated using RMSEA, CFI, CMIN/DF and SRMR. Findings- Results reveal that all four independent factors significantly influence investing choices and investment return is a major mediator. The largest direct influences on returns were those of investing goals and investment horizon, which then shaped choices. Strong internal consistency and dependability let the model show an excellent fit. Implications- Using these realizations, fund managers may create mutual funds that complement investor objectives, hence improving fund attractiveness and performance. Policymakers may regulate mutual funds to promote transparency and good judgment. Originality/Value- This research addresses Nepal's growing mutual fund market and meets a need for data on investing factors. A detailed strategy and robust methodology give informative research on developing financial market investment behavior. Int. J. Soc. Sc. Manage. Vol. 12, Issue-2: 89-98.